Aglomeração econômica e disparidade salarial no Espírito Santo : teoria e evidência a partir de um enfoque da nova geografia econômica - Breda, Diogo Dias (2014)
The study sought to examine issues of regional inequality in the Espírito Santo through the research line called New Economic Geography (NEG). One way to accomplish this analysis is through the study of the relationship between wage differentials and market potential. Specifically, the study sought to investigate the impact of geographic factors of second nature – market potential – in the local average wage. Initially, through an Exploratory Spatial Data Analysis, it was found that the wages are higher near the regions with high market potential (coastal/ RMGV). Through the use of statistical and spatial econometrics techniques was observed for the years 2000 and 2010 the existence of a spatial wage structure in the Espírito Santo. The autoregressive error coefficient λ is positive and statistically significant, indicating spatial error model as the most appropriate for modeling the spatial effects. The results also indicate that not only educational factors affect wages, geographical factors of second nature have an even greater effect when compared to the previous. In conclusion, as demonstrated by the central model of NGE, market forces by itself do not always lead to equalizer equilibrium of yields, on the contrary, lead to formation of a structure of core-periphery with persistent income gap between regions. Municipalities with higher salary, larger market potential and better social indicators are those located on the coast of the state, more precisely near RMGV. The study underscores the need to think strategies that promote the creation of new centralities, in order to act on reducing regional inequalities. The work is part of a group of several other studies that examined issues of inequality and productive concentration in the Espírito Santo. The contribution is to use the theoretical framework of NGE, which had not yet been employed for the state, and the use of techniques of spatial statistics and spatial econometrics.